Research on the Vibration Isolation Characteristics of Floor Vibration Isolation Slab System under Train Operation - Jinbao Yao; Han Wu; Shaoyin Tao (Advances in Civil Engineering)
This study takes the vibration isolation measures of building floor vibrations induced by trains as the starting point and carries out both theoretical derivation and numerical simulation. A four-degree-of-freedom (DOF) multi-dimensional vibration isolation platform (VIP) dynamics model is established based on the theoretical research of single-level, single-degree-of-freedom vibration isolation systems. Under multi-point excitation, the model can deduce the horizontal and vertical vibration responses of the VIP system. A comprehensive analysis of the vibration isolation performance of the VIP system on the floor and how the variation of the parameters influences the performance of the vibration isolation systems are presented. Several variables, such as the thickness, stiffness, damping ratio, and the number of isolators of the VIP system, are theoretically found to have a significant impact on the vibration isolation effect of the floor VIP system. Empirical results show that the VIP system significantly affects the vibration isolation of the building floor induced by a train and has the best vibration isolation effect on the acceleration response and the worst vibration isolation effect on the displacement response.